Through Chapter 11 with Gun or Camera, but Probably Not Both: A Field Guide - John D. Ayer (Washington University Law Quarterly, 1994)
The purpose of this Article is to offer some clarification in the interest of complication.
Keywords: Bankruptcy Code of 1978; Bankruptcy; Law & economics; Bankruptcy reorganization